Penerapan Model Project Based Learning Pada Mata Pelajaran Sejarah Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas X.2 SMA Negeri 22 Palembang - Mailiza Hidayati, Yusnidar, L.R. Retno Susanti (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2024)
This study is entitled " The Implementation of Project Based Learning Model in the subject of History, Specifically on the material of Process of the Arrival of Islam in Indonesia, to Improve the Learning Outcomes of grade X.2 Students at 22nd State Senior High School in Palembang". This study was motivated by the low of learning outcomes from students of the X.2 class caused by a learning model that was not yet interactive. Based on this background, the researcher formulates the problem namely whether the implementation of the independent learning curriculum with the application of Project Based Learning can improve the learning outcomes for students of the X.2 class in the History Subject matter of the Process of the Arrival of Islam in Indonesia. The aim of the study is to apply the Project Based Learning model in the implementation of the independent learning curriculum to improve the learning outcomes for students of the X.2 class in learning the history of the arrival of Islam in Indonesia. This study used the Classroom Action Research (CAR) method with the research design by Rustiyarso and Tri Wijaya, starting from action planning, action implementation, observation, and reflection which consisted of 2 cycles. The results of this study indicate that learning outcomes have increased in each cycle. In the initial condition stage (Pre-cycle) the classical mastery obtained was 45%, in the first cycle stage the classical mastery was achieved 76% and in the second cycle stage the classical completeness was 88%.